الجيش الروماني وأزمة القرن الثالث الميلادي (235/284م) (Journal of Humanitarian and Applied Sciences, 2023)
The army played a prominent role in the deterioration of the conditions of the empire during the third century, when it intervened in political affairs and isolated and appointed emperors. This resulted in a bitter conflict in which the army played a major role and caused unrest and instability. Each division sought to bring its leader to the imperial throne, or appointed the one who would pay the highest price in the imperial throne, or according to the ability of the one who aspires for to bribe soldiers. In addition, the empire lost a strong central government that ran its affairs at that time. However, most of the emperors' concern was to maintain the army's loyalty to ensure its continued seating on the throne, in addition to imposing taxes to raise money to pay soldiers' salaries. During this period, the Romanian army became the one who enjoyed the fruits of the empire in the third century A.D., and it became the actual controller, increasing the number of military divisions, doubling salaries, granting soldiers the right to marry in service, and the military dictatorship and the power of forces over the rulers became harmful and beneficial. On the one hand, it committed the army to protect the empire, but this defense of the empire led it to pride and domination, and to consolidate the military dictatorship with all its might. The third century was characterized by the domination of the soldiers and the army became very powerful and influential. Instead of being ruled by the army, the emperor was ruled by the emperor. The domination of the military leaders led to internal instability. As a result of the chaos that had befallen the army and its preoccupation with political matters, the external threat had intensified and the peoples around the empire were emboldened and attacked the borders.